2000
DOI: 10.1073/pnas.97.26.14376
|View full text |Cite
|
Sign up to set email alerts
|

An alternative, nonapoptotic form of programmed cell death

Abstract: The term apoptosis often has been used interchangeably with the term programmed cell death. Here we describe a form of programmed cell death that is distinct from apoptosis by the criteria of morphology, biochemistry, and response to apoptosis inhibitors. Morphologically, this alternative form of programmed cell death appears during development and in some cases of neurodegeneration. Despite its lack of response to caspase inhibitors and Bcl-x L, we show that this form of cell death is driven by an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
791
4
9

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 860 publications
(834 citation statements)
references
References 42 publications
30
791
4
9
Order By: Relevance
“…Although initially disputed, several forms of caspase-independent apoptosis [33][34][35] or forms that are similar to apoptosis ('paraptosis') but also do not involve caspases have been reported. 30,36 Sperandio and colleagues (2000) characterized 'paraptosis' in 293T cells and mouse embryonic fibroblasts as a form of cell death without nuclear fragmentation and apoptotic bodies, but with cytoplasmic vacuolation and late mitochondrial swelling. In addition, death was independent of caspase activity, Bcl-X L , and was executed without DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initially disputed, several forms of caspase-independent apoptosis [33][34][35] or forms that are similar to apoptosis ('paraptosis') but also do not involve caspases have been reported. 30,36 Sperandio and colleagues (2000) characterized 'paraptosis' in 293T cells and mouse embryonic fibroblasts as a form of cell death without nuclear fragmentation and apoptotic bodies, but with cytoplasmic vacuolation and late mitochondrial swelling. In addition, death was independent of caspase activity, Bcl-X L , and was executed without DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that neuronal death induced by either potassium deprivation or blocking the NHE is mediated by different cell death pathways. Sperandio et al (2000) 30 recently introduced the concept of 'paraptosis', an alternative, nonapoptotic form of programmed cell death, that did not show a response to caspase inhibitors and Bcl-X L , but to cycloheximide. Treatment with cycloheximide blocked the death of cerebellar granule neurons after potassium withdrawal and after treatment with HOE 642 (Figure 7a).…”
Section: Death Of Cerebellar Granule Neurons Induced By Hoe 642 or Eimentioning
confidence: 99%
“…It has been suggested that, when caspases are inhibited, other factors, released from mitochondria in a caspase-independent manner, can trigger a secondary nonapoptotic form of death. 17 Apoptosis-inducing factor (AIF 18 ) has been related to a nonapoptotic morphotype in several cell types and conditions, for example, Apaf1 À/À interdigital web cells 19 and primary hippocampal neurons. 20 More recently, the independence of AIF release from caspase activation has been questioned.…”
Section: Etna Cells Apoptosis Induced By Neurodegenerative Stimuli Ismentioning
confidence: 99%
“…Although pcd has often been equated with apoptosis, it has become increasingly clear that nonapoptotic forms of pcd also exist. [1][2][3][4][5][6][7][8][9][10][11][12][13] For example, certain developmental cell deaths, such as 'autophagic' cell death [1][2][3][4][5] and 'cytoplasmic' cell death, 2,4,6-9 do not resemble apoptosis. Furthermore, neurodegenerative diseases such as Huntington's disease and amyotrophic lateral sclerosis demonstrate neuronal cell death that does not fulfill the criteria for apoptosis.…”
Section: Introductionmentioning
confidence: 99%